Dry carbonate process for CO2 capture and storage: Integration with solar thermal power. (February 2018) - Bonaventura, D.; Chacartegui, R.; Valverde, J.M.; Becerra, J.A.; Ortiz, C.; Lizana, J.
Abstract: Capture and sequestration of CO2 released by conventional fossil fuel combustion is an urgent need to mitigate global warming. In this work, main CO2 capture and sequestration (CCS) systems are reviewed, with the focus on their integration with renewables in order to achieve power plants with nearly zero CO2 emissions. Among these technologies under development, the Dry Carbonate Process shows several advantages. This manuscript analyses the integration of a CO2 sorption-desorption cycle based on Na2 CO3 /NaHCO3 into a coal fired power plant (CFPP) for CO2 capture with solar support for sorbent regeneration. The Dry Carbonate Process relies on the use of a dry regenerable sorbent such as sodium carbonate (Na2 CO3 ) to remove CO2 from flue gases. Na2 CO3 is converted to sodium bicarbonate (NaHCO3 ) through reaction with CO2 and water steam. Na2 CO3 is regenerated when NaHCO3 is heated, which yields a gas stream mostly containing CO2 and H2 O. Condensation of H2 O produces a pure CO2 stream suitable for its subsequent use or compression and sequestration. In this paper, the application of the Dry Carbonate CO2 capture process in a coal-based power plant is studied with the goal of optimizing CO2 capture efficiency, heat and power requirements. Integration of this CO2 capture process requires an additional heat supply which would reduce the global power plant efficiency by around 9–10%. Dry Carbonate Process has the advantage compared with other CCS technologies that requires a relatively low temperature for sorbent regeneration (< 200 °C). It allows an effective integration of medium temperature solar thermal power to assist NaHCO3 decarbonation. This integration reduces the global system efficiency drop to the consumption associated with mechanical parasitic consumption, resulting in a fossil fuel energy penalty of 3–4% (including CO2 compression). The paper shows the viability of the concept through economic analyses under different scenarios. The results suggest the interest of advancing in this Solar-CCS integrated concept, which shows favourable outputs compared to other CCS technologies.